Fast-Track Rapid Warfarin Reversal for Elective Surgery: Extending the Efficacy Profile to High-Risk Patients with Cancer. Issue 6 (November 2015) - Byrne, T. J.; Riedel, B.; Ismail, H. M.; Heriot, A.; Dauer, R.; Westerman, D.; Seymour, J. F.; Kenchington, K.; Burbury, K.
Periprocedural management of patients on long-term warfarin therapy remains a common and important clinical issue, with little high-quality data to guide this complex process. The current accepted practice is cessation of warfarin five days preoperatively, but this is not without risk and can be complicated, particularly if bridging is required. An alternative method utilising low-dose intravenous vitamin K the day before surgery has been shown previously to be efficacious, safe and convenient in an elective surgical population receiving chronic warfarin therapy. The efficacy and utility of this 'fast-track' warfarin reversal protocol in surgical patients with cancer, who were at high risk of both thromboembolism and bleeding was investigated in a prospective, single-arm study at a dedicated cancer centre. Seventy-one patients underwent 82 episodes of fast-track warfarin reversal (3 mg intravenous vitamin K 18 to 24 hours before surgery). No patient suffered an adverse reaction to intravenous vitamin K, all but one achieved an International Normalized Ratio ≤1.5 on the day of surgery, and no surgery was deferred. Assays of vitamin K–dependent factor levels pre- and post-vitamin K demonstrated restoration of functional activity to within an acceptable range for surgical haemostasis. While this alternative method requires further validation in a larger prospective randomised study, we have now extended our use of fast-track warfarin reversal using vitamin K to patients with cancer, on the basis of our experience of its safety, convenience, reliability and efficacy.